The impact of institutional dimensions on entrepreneurial intentions of students: International evidence - Yassine Bakkar; Susanne Durst; Wolfgang Gerstlberger (Journal of Risk and Financial Management, 2021)
Acknowledging the role of different forms of entrepreneurship to continued economic prosper-ity and the role of institutional dimensions on entrepreneurship, this paper investigates if and to what extent a selected number of institutional dimensions influence students' intentions to ei-ther start a company or take over an existing one. Based on a Global University Entrepreneurial Spirit Students' Survey (GUESS) dataset and international country-level databases, evidence shows that both entrepreneurship options are hampered by corruption and limited business freedom while promoted through favourable labour regulations and trade freedom. Property rights, fiscal freedom, government spending, monetary freedom, and investment freedom only affect start-ups, while financial freedom adversely affects both options. The study provides new insight into the impact of institutional dimensions on different types of entrepreneurship. Thus, in contrast to extant research in this area, it goes beyond the typical focus on start-ups. Evidence also suggests that male students prefer starting a new company, while female students seem to prefer a takeover. This improved understanding could help in not only designing more targeted entrepreneurship and entrepreneurial financing policies but also in improving entrepreneurship education.
Keywords: 330; entrepreneurial activity; entrepreneurial intentions; institutional dimensions; start-ups; students; takeovers